Degradation of a Textile Dye C. I. Direct Red 80 by Electrochemical Processes - Lopes,A. (2004)
The electrochemical removal of the textile dye C. I. Direct Red 80 (DR80) was carried out using three different materials as anodes: iron, polypyrrole (PPy) and boron doped diamond (BDD). Iron electrodes are consumed during the electrolysis, and promote flocculation/coagulation of the dye. Polypyrrole, a conducting polymer, was prepared by chemical/electrochemical precipitation over a cotton cloth; it enables the precipitation of the dissolved dye through a conversion reaction in a less soluble compound. Boron doped diamond electrode was used to achieve the complete mineralization of the dye. Bulk electrolysis were studied using Na2SO4 as electrolyte. In the case of the PPy electrode, NH4NO3 was also used as electrolyte. The variation of the dye concentration was followed by UV-visible absorbance measurements and chemical oxygen demand (COD) tests were also performed, to compare the rates of colour and COD removal in each case. From the COD measurements over the time of electrolysis, using the BDD anode, a mass transfer coefficient for the DR80 molecule was determined. The obtained results show an almost complete colour removal for all the electrodes tested and a COD removal between 50 and 90 %, being the best results obtained with the BDD electrode.